Extrapelvic Endometriosis: Two Case Reports - Egemen Tolunay; İbrahim Yalçın; Bulut Varlı; Alper Kahraman; Murat Seval; Murat Sönmezer; Cem Atabekoğlu (Gynecology Obstetrics & Reproductive Medicine)
Endometriosis is the growth of endometrial cells outside the uterine cavity. Most common localizations are pelvic organs and peritoneum. Endometriosis mostly affects women in their reproductive years. After surgery it can be seen on the abdominal wall. This article includes two patients, one has abdominal wall endometriosis and the other has inguinal endometriosis. Both of them had surgical excision without recieving any medical treatment.